2009
DOI: 10.1126/science.1167130
|View full text |Cite
|
Sign up to set email alerts
|

Control of Graphene's Properties by Reversible Hydrogenation: Evidence for Graphane

Abstract: Graphene -a monolayer of carbon atoms densely packed into a hexagonal lattice (1)-

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

160
3,592
15
37

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 3,929 publications
(3,804 citation statements)
references
References 30 publications
160
3,592
15
37
Order By: Relevance
“…[12] The broad sensing potential of graphene can only be unlocked by the introduction of sensitizer (bio)molecules and structures, e.g. various inorganic groups, [23][24][25][81][82][83][84][85][86][87][88][89][90] organic or organometallic molecules, [37,[91][92][93][94][95][96] DNAs, [97][98][99][100][101] proteins, [102] peptides, [30,31,103,104] nanoparticles, [105,106,107] and 2D heterostructure. [51,52,61,108] These molecules are able to respond chemically or physically to their nearby environment, whose responses could then be transduced into an appreciable change in the conductivity of the carbon-based honeycomb scaffold.…”
Section: Meeting the Challenges In Chemical Functionalization Of Grapmentioning
confidence: 99%
See 1 more Smart Citation
“…[12] The broad sensing potential of graphene can only be unlocked by the introduction of sensitizer (bio)molecules and structures, e.g. various inorganic groups, [23][24][25][81][82][83][84][85][86][87][88][89][90] organic or organometallic molecules, [37,[91][92][93][94][95][96] DNAs, [97][98][99][100][101] proteins, [102] peptides, [30,31,103,104] nanoparticles, [105,106,107] and 2D heterostructure. [51,52,61,108] These molecules are able to respond chemically or physically to their nearby environment, whose responses could then be transduced into an appreciable change in the conductivity of the carbon-based honeycomb scaffold.…”
Section: Meeting the Challenges In Chemical Functionalization Of Grapmentioning
confidence: 99%
“…[22] Additionally, graphene (at least ideal graphene) has a crystal lattice free of dangling bonds and is therefore intrinsically chemically inert. This inertness has been a driving force for the first attempts aiming at biointerfacing graphene with specific recognition moieties, via both covalent [23][24][25][26][27]28] and non-covalent [29][30][31][32] approaches, using different biochemical molecules and chemical treatments.…”
Section: Introduction: Challenges and Opportunitiesmentioning
confidence: 99%
“…Physisorption of chemical species on graphene would provide a facile way to alter its electronic properties 12 , however, covalent chemical modification shows a great advantage in achieving permanent stabilisation for long-term usage 13 . Previous attempts towards fundamental research on covalent functionalisation of graphene mainly involved the development of new modification strategies (for example, hydrogenation [14][15][16][17] , fluorination [18][19][20] , chlorination 21,22 , diazotization [23][24][25][26][27] and other cycloaddition reactions [28][29][30][31] ), covalent addition of edge and defects 27,32 , fabrication of chemical superlattices 26,33 and quantum effects in graphene modification 17,34 . Of the various significant research activities on graphene chemistry that have been conducted, nearly no work to date has been focused on the asymmetric chemistry of this ideal 2D atomic crystal via covalently attaching different functional groups on its two faces simultaneously.…”
mentioning
confidence: 99%
“…This is a prerequisite for its bifacially nonsymmetrical modification. Previous works have shown that free-standing graphene exhibits higher chemical functionalisation extent at the same condition in comparison with graphene supported by a substrate, because only one side of the latter is accessible to the reactants 14,18 . This unique property, as well as the availability of various approaches towards graphene functionalisation, allows us to further develop a facile approach to engineering graphene nonsymmetrically, by attaching its two sides with different functionalities.…”
mentioning
confidence: 99%
“…Hydrogen adsorption on carbon based materials such as graphite and graphene is relevant to hydrogen storage, 9 band gap engineering, [10][11][12][13] and potentially as the first step in H 2 formation in the interstellar medium. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Although there is enormous interest in H adsorption on carbonaceous surfaces, with graphene, graphite and polycyclic aromatic hydrocarbons (PAHs) being the most widely studied model systems, we still don't fully understand the seemingly simple process of how a single H atom adsorbs on the surface.…”
mentioning
confidence: 99%